THE EFFECT OF THE FRAUD TRIANGLE IN DETECTING FRAUDULENT FINANCIAL REPORTING IN INDONESIAN BANKING SECTOR COMPANIES - Ricardo, Rico; Suhendah, Rousilita (International Journal of Application on Economics and Business, 2023)
This research aims at finding out the influence of factors in fraud triangle theory towards fraudulent financial reporting in banking companies in Indonesia. Research sample was chosen by using some criteria that consist of banking sector companies registered and listed in Indonesian Stock Exchange & Bank Based on Business Activity II, III, IV group from 2017 to 2019. These criteria chose 37 banks as sample processed by e-Views 12 and Microsoft Excel application. Fraud triangle theory divides three fraud factors: pressure, opportunity, and rationalization. Pressure factor includes external pressure and financial target. Opportunity factor is reflected by monitoring variable, and rationalization factor consists of auditor change and accrual method variable. Research results show that independent variables gave significant impact to dependent variable, except for monitoring and auditor change variable.